INCREASING THE CAPACITY OF POSYANDU AGENTS THROUGH STUNTING PREVENTION EDUCATION IN CREATING HEALTHY CHILDREN IN SANCA VILLAGE, CIATER REGENCY - Sumardani; Yuyun Yuningsih; Ikhsan Maulana (LPM Universitas Pasundan, 2024)
Stunting is a severe condition in children characterized by a child's height above lower average or child concise as well as her body no grow and developing well according to age and lasting for a long time, even at the end followed by the disturbance in intelligence in children due to lack of chronic nutrition. This condition is triggered by several factors in the mother's womb, including infection in pregnancy, malnutrition (malnutrition) in pregnant women, which is not optimal for the baby from since born until three years of first life, repeated infections, or poor stimulation from the environment. According to Law Number 36 of 2009 concerning Health, the community must participate properly by per scarecrow and organized in all forms and stages of health development in order to help accelerate the achievement of the highest level of public Health. According to the survey results in Sanca Village, it is known that some of the problems encountered with monitoring activities are known growth of toddlers. Posyandu, known as Integrated Healthcare Center, including eight posyandu in 2021, categorized as an independent Posyandu in Sanca Village, which consists of 8 RW, and each posyandu opening schedule is not in accordance with the wishes of the community, as well as the whole the schedule is determined by the Puskesmas or the Village. The number of active cadres is only five people per posyandu. In practice, there are still difficulties for posyandu agents intake measurements anthropometry by appropriate.